THE INTERNET: BREAKING THE RULE OF TEACHING GRAMMAR - Antonius Suratno (Celt: A Journal of Culture, English Language Teaching & Literature, 2007)
III this paper the writer reports the use of the Internet as part of strategy in teaching grammar of English. In such a case, students managed to both experience the wealth of computer technology through the Internet abundant facilities for learning language and the success in grasping better ideas of the language rules. Through this activity, students functioned as "active explorer" of the rule of the language and as such were motivated to invest time and energy into their unusually interesting and challenging . structure class. Students were put into groups with which they went exploring the Internet to find out the predetermined topic of exercises and practiced it together in groups, printed it out and then accounted for it in front of the class. They had to be able to defend their answer in front of the class and to be ready 10 explain their answer. Based on The observation made during the running of the class, the writer found that this teaching method allows students to more experience structure of English. Then, from their comments they admitted that they learned structure better as they feel they were challenged to experience more than the ordinary book-based class.